Struggles for Reproductive Justice in the Era of Anti-Genderism and Religious Fundamentalism - Selberg, Rebecca; Kolankiewicz, Marta; Mulinari, Diana (Springer Nature, 2023)
This open access book engages with the concept of reproductive justice by exploring case studies of struggles around abortion in the context of rising anti-genderism, religious fundamentalism, and ethno-nationalism. Based on rich qualitative data offering in-depth analyses from different geographical, political and cultural contexts, the book explores how reproductive justice is understood, contested and given meaning. Chapters further develop the Black feminist concept of reproductive justice in a critical dialogue with postcolonial theory and explore the strength of transnational feminist practices. This book thus offers a fresh approach to the issue of abortion by engaging with contemporary political and cultural processes, and it expands the narrow notions of women's rights, particularly notions of property rights over bodies, towards an analysis of the political economy of social reproduction and how it affects bodies that can be pregnant. This volume will be of interest to scholars with interests in reproductive justice, anti-gender politics, and religious fundamentalism.